Cancer stem cells as a therapeutic target in 3D tumor models of human chondrosarcoma: An encouraging future for proline rich polypeptide-1 - Granger, Caroline J. (Mol Med Rep, 2020)
Chondrosarcoma is a malignant bone neoplasm that is refractory to chemotherapy and radiation. With no current biological treatments, mutilating surgical resection is the only effective treatment. Proline rich polypeptide 1 (PRP-1), which is a 15-amino acid inhibitor of mammalian target of rapamycin complex-1 (mTORC1), has been indicated to exert cytostatic and immunomodulatory properties in human chondrosarcoma cells in a monolayer. The aim of the present study was to evaluate the effects of PRP-1 on an in vitro 3D chondrosarcoma tumor model, known as spheroids, and on the cancer stem cells (CSCs) which form spheroids. JJ012 cells were cultured and treated with PRP-1. An ALDEFLUOR™ assay was conducted (with N,N-diethylaminobenzaldehyde as the negative control) to assess aldehyde dehydrogenase (ALDH) activity (a recognized CSC marker), and bulk JJ012, ALDH(high) and PRP-1 treated ALDH(low) cells were sorted using flow cytometry. Colony formation and spheroid formation assays of cell fractions, including CSCs, were used to compare the PRP-1-treated groups with the control. CSCs were assessed for early apoptosis and cell death with a modified Annexin V/propidium iodide assay. Western blotting was used to identify mesenchymal stem cell markers (STRO1, CD44 and STAT3), and spheroid self-renewal assays were also conducted. A clonogenic dose-response assay demonstrated that 20 µg/ml PRP-1 was the most effective dose for reducing colony formation capacity. Furthermore, CSC spheroid growth was significantly reduced with increasing doses of PRP-1. Annexin V analysis demonstrated that PRP-1 induced CSC cell death, and that this was not attributed to apoptosis or necrosis. Western blot analysis confirmed the expression of mesenchymal markers, and the spheroid self-renewal assay confirmed the presence of self-renewing CSCs. The results of the present study demonstrate that PRP-1 eliminates anchorage independent CSC growth and spheroid formation, indicating that PRP-1 likely inhibits tumor formation in a murine model. Additionally, a decrease in non-CSC bulk tumor cells indicates an advantageous decline in tumor stromal cells. These findings confirm that PRP-1 inhibits CSC proliferation in a 3D tumor model which mimics the behavior of chondrosarcoma in vivo.